Induction of HSP70 shows differences in protection against I/R injury derived by ischemic preconditioning and intermittent clamping - Zapletal, Christina; Fallsehr, Christine; Reidel, Margot; Löffler, Thorsten; Gebhard, Martha-Maria; Golling, Markus T.; Klar, Ernst (Microvascular research, 2010)
Background - Ischemic preconditioning (IP) and intermittent clamping (IC) increase the ischemic tolerance of the liver. The underlying mechanisms are not completely understood. Heat shock proteins protect cellular integrity in stress and have been discussed as mediators in preconditioning. IP and IC in rat livers were compared with respect to HSP induction and postischemic microcirculation. - Methods - All animals were exposed to 70min of partial warm liver ischemia. Different clamping protocols were used: in control animals (C) 70min continuous ischemia was applied. IP was performed by 5min ischemia and 10min reperfusion before the 70min ischemia time. In IC-groups, ischemia time of 70min was divided into four intervals. Each group included 21 animals with 3 different reperfusion intervals; either 30min, 12 or 36h. Intravital microscopy was performed after 30min of reperfusion. AST-levels and HSP induction were analysed 90min, 12 and 36h after reperfusion. - Results - IP and IC significantly improved sinusoidal perfusion (IP: 83.4±2.8%; IC: 84.4±4.6% vs. C: 60.4±3.9%; p<0.001) and leucocyte adherence in sinusoids (IP: 51.9±12.0, IC: 40.9±4.7 vs. C: 90.1±17.7/mm2 liver surface; p<0.001) and postsinusoidal venules. AST-levels were minimized in IP and IC compared to controls (12h after reperfusion: IP: 969±934U/l, IC: 675±562U/l vs. C: 2373±792U/l; p=0.004). In the course of reperfusion HSP70 protein expression doubled between 90min and 12h in IC (0.529±0.227 vs. 0.992±0.246; p<0.05) and control-groups (0.572±0.314 vs. 1.106±0.309; p<0.05) whereas it remained unchanged in the IP-group (0.437±0.383 vs. 0.412±0.439; n.s.). - Conclusion - Microcirculation is similarly preserved by IP and IC. The early protection derived by IP prevents further induction of HSP70 in opposite to IC. Therefore, IP may offer a more comprehensive protection against I/R on a cellular and transcriptional level.